Synchronization of optically coupled resonant tunneling diode oscillators - Romeira, B.; Figueiredo, J.; Ironside, Charlie; Quintana, J. (2013)
We experimentally investigate the synchronous response of two fiber-optic coupled optoelectronic circuit oscillators based on resonant tunneling diodes (RTDs). The fiber-optic synchronization link employs injection of a periodic oscillating optical modulated signal generated by a master RTD-laser diode (LD) oscillator to a slave RTD-photodetector (PD) oscillator. The synchronous regimes were evaluated as a function of frequency detuning and optical injection strength. The results show the slave RTD-PD oscillator follows the frequency and noise characteristics of the master RTD-LD oscillator resulting in two oscillators with similar phase noise characteristics exhibiting single side band phase noise levels below -100 dBc/Hz at 1 MHz offset from the carrier frequency. Optical synchronization of RTD-based optoelectronic circuit oscillators have many applications spanning from sensing, to microwave generation, and data transmission. © 2013 SPIE.